APOL1 polymorphisms are not influencing acute coronary syndrome risk in Czech males - Hubacek, Jaroslav A; Adamkova, Vera; Lanska, Vera; Stanek, Vladimir; Mrazkova, Jolana; Gebauerova, Marie; Kettner, Jiri; Kautzner, Josef; Pitha, Jan (Molecular genetics & genomic medicine, 2024)
BACKGROUND: The highest mortality and morbidity worldwide is associated with atherosclerotic cardiovascular disease (ASCVD), which has in background both environmental and genetic risk factors. Apolipoprotein L1 (APOL1) variability influences the risk of ASCVD in Africans, but little is known about the APOL1 and ASCVD in other ethnic groups. METHODS: To investigate the role of APOL1 and ASCVD, we have genotyped four (rs13056427, rs136147, rs10854688 and rs9610473) APOL1 polymorphisms in a group of 1541 male patients with acute coronary syndrome (ACS) and 1338 male controls. RESULTS: Individual APOL1 polymorphisms were not associated with traditional CVD risk factors such as smoking, hypertension or diabetes prevalence, with BMI values or plasma lipid levels. Neither individual polymorphisms nor haplotypes were associated with an increased risk of ACS nor did they predict total or cardiovascular mortality over the 10.2 ± 3.9 years of follow-up. CONCLUSIONS: We conclude that APOL1 genetic variability has no major effect on risk of ACS in Caucasians.
Keywords: senioři; běloši; Genetic Predisposition to Disease; Caucasians; jednonukleotidový polymorfismus; Česká republika; apolipoproteiny; apolipoprotein L1; polymorphism; Middle Aged; Haplotypes; mužské pohlaví; studie případů a kontrol; Apolipoprotein L1; Czech Republic; Lipoproteins, HDL; Apolipoproteins; Humans; lipoproteiny HDL; haplotypy; lidé středního věku; rizikové faktory; White People; akutní koronární syndrom; cardiovascular disease; Case-Control Studies; genetická predispozice k nemoci; Risk Factors; Aged; mortality; Acute Coronary Syndrome; lidé; Male; Polymorphism, Single Nucleotide